Information seeking by blind and sight impaired citizens: an ecological study (Information Research: An International Electronic Journal)
The article reports a study which investigated information seeking by blind and sight impaired people, with particular emphasis on the role of the Internet. A literature review revealed a paucity of studies about the information-seeking behaviour of groups of people with disabilities, including blind and sight impaired people. The study focussed very specifically on both personal lives and broader social contexts. The techniques for collecting qualitative data included two focus groups involving 16 participants and 15 individual interviewees, from both city and country settings. The findings of the study address issues of information needs, information sources, the role of the Internet in meeting needs and the barriers to the use of the Internet. A major conclusion is that people who are blind and sight impaired deserve to be provided with a range of ways of meeting information needs, as are available for people with normal sight. Given the inexorable continuing impact of the information age, it is also concluded that ways must be found so that people with disabilities can participate equitably in the information economy.